Distribution of the tick Dermacentor reticulatus in the United Kingdom. Issue 3 (17th April 2017) - MEDLOCK, J. M.; HANSFORD, K. M.; VAUX, A. G. C.; CULL, B.; ABDULLAH, S.; PIETZSCH, M. E.; WALL, R.; JOHNSON, N.; PHIPPS, L. P.
Abstract : The recent implication of Dermacentor reticulatus (Ixodida: Ixodidae) in the transmission of canine babesiosis in the U.K. has highlighted the lack of accurate published data on its distribution in this country. This paper aims to collate and appraise historical data for D. reticulatus, to supplement such data with more recent surveillance data and to report on field sampling conducted during 2009–2016. These updated data facilitate better understanding of the current distribution of this tick in the U.K., which will better inform disease risk assessments. There appear to be four known regions of the U.K. in which D. reticulatus currently occurs, including western Wales, North and South Devon, and Essex. The majority of foci are located in coastal sand dunes and maritime grasslands, including grazing marsh. However, more recently the tick has been detected in urban greenspace in Essex. The emergence of this tick as a vector of babesiosis in the U.K. and its recent apparent spread in Essex into urban greenspace highlight the need for continued surveillance and for further research into its status as a vector of human and veterinary pathogens.